Scientific publishing from Marmara University: Contribution of the School of Medicine - (:unkn) unknown (My University, 1996)
Objective : International journals are indexed in different indexes but 'Science Citation Index' appears to be the most widely recognized and respected one of these. In this study, papers published in journals covered by the 'Science Citation Index' have been reviewed and contribution made by different departments of the Medical School was investigated. This paper also aims to find out the position of the Medical School in Marmara University. Methods : In this study, papers published in journals covered by 'Science Citation Index' from 1984 to 1994 have been reviewed and contribution made by Marmara University and the School of Medicine was investigated. Results : The number of papers from Marmara University increased from one in 1984 to 52 in 1994. During this period, a total of 142 papers were published by the Medical School and the contribution of the Medical School to the total number of papers from Marmara University demonstrated a steady increase reaching 77% in 1994. Like the total number of published papers, the number of papers per teaching staff has also shown progress during this time period. The papers were written from 24 different departments of the Medical School. Conclusion: We believe that with more and effective contribution of every faculty and department, better scientific ranking can be obtained for both Mamara University and the Medical School.
Keywords: Marmara University; School of Medicine; Scientific publication